Body plasticity in borderline personality disorder: a link to dissociation - Bekrater-Bodmann, Robin; Gescher, Dorothee Maria; Bohus, Martin; Flor, Herta (Comprehensive psychiatry, 2016)
Introduction Patients with borderline personality disorder (BPD) often report an unstable sense of self, which is further enhanced in dissociative states. As one consequence, BPD patients show a labile body percept, which might result in a higher degree of body plasticity. However, experimental data on body plasticity in BPD are not yet available. Materials and methods The rubber hand illusion (RHI) probes the plasticity of one's body by inducing the feeling of ownership for an artificial limb. We tested the proneness to perceive the RHI in female patients with current and remitted BPD compared to healthy controls, and related their perceptions to state and trait dissociation. Results Participants with current BPD, compared to healthy controls, reported higher proneness to perceive the RHI (p<.05, with an effect size [Cohen's d] of 0.68). Remission was associated with a stabilization of perceptions. RHI vividness was positively related to state and trait dissociation across the groups, and specifically in current BPD when controlling for symptom severity (all Pearson's r≥.30, p<.05). Discussion These results indicate enhanced body plasticity related to dissociation in BPD, point to shared neurobiological mechanisms, and might help to elucidate the body-related perceptual disturbances associated with BPD. Conclusion The results provide initial empirical evidence for significant alterations in body ownership processing associated with a current BPD diagnosis, resulting in enhanced body plasticity. Dissociation significantly correlated with illusory limb ownership experiences, making body plasticity a marker for BPD.
Gesehen am 29.11.2018